Immunophenotyping of Rabbit Testicular Germ and Sertoli Cells Across Maturational Stages. (November 2016) - Banco, B.; Grilli, G.; Giudice, C.; Marques, A. Tomas; Cotti Cometti, S.; Visigalli, G.; Grieco, V.
During testicular maturation, both Sertoli cells (SCs) and germ cells (GCs) switch from an immature to a mature immunophenotype. The reexpression of markers of immaturity in adults has been reported in cancer and in other testicular pathologies, in men as well as in animal species. Naturally affected with testicular cancer, rabbits have long been used in human reproductive research, but reports on the expression of testicular cell markers in this species are few and data about the immunophenotype of normal postnatal SCs and GCs are lacking. The aim of this study was to investigate the immunophenotype of SCs and GCs in the rabbit, from neonatal to adult age, using the antibodies anti-Müllerian hormone (AMH), vimentin (VIM), CKAE1/AE3 (cytokeratins [CKs]), desmin (DES), inhibin alpha (INH-α), placental alkaline phosphatase (PLAP), and periodic acid–Schiff (PAS) staining. In SCs, VIM was constantly expressed, and AMH and CKs expression was limited to neonatal and prepubertal age, whereas DES, INH-α, PLAP, and PAS were constantly negative. GCs were negatively stained for PLAP, PAS, and for the other markers. Results revealed analogies with human testicular immunophenotype, suggesting that rabbits could represent a potential experimental model for the study of human testicular pathology.